KARAKTERISTIK CALON PAMONG BERCIRIKAN TAMANSISWA MENGHADAPI ERA MEA 2015 - Siti Mariah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
The purpose of this research was to determine the characteristics of teacherâ€™s candidates with Tamansiswa distinctive features on students of PKK UST. The research was done by using a descriptive-exploratory survey. This research includes experts of Tamansiswa as "expert judgment" to formulate the indicators of teacherâ€™s candidate with Tamansiswa distinctive features. The populations in this study are students of PKK FKIP UST, using a purposive sampling technique to 27 students of 2010-2011 who are still active and have been carrying out teaching practice. The collection of data is through questionnaires with descriptive analysis techniques using percentage calculation. The results showed that there are 19 characteristicsâ€™ indicators of teacherâ€™s candidates with Tamansiswa distinctive features: religious, orderly, ngandel-kendel, kandel, tolerant, corrective, tripantangan, self-control, wening-bening, cooperative, with the spirit of nationalism, consultative, antep, tetep, independent soul, Tut wuri handayani, Ing madyo mangun karso, Ing ngarso sung tulodo. The characteristic of teacherâ€™s candidates with Tamansiswa distinctive features on students of PKK UST under the category of ngerti, ngroso, nglakoni is that most PKK students are in the category of always "ngerti", a few students are in the category of sometimes â€œngertiâ€, there are very few students who never â€œngertiâ€ with a very little frequency on tripantangan indicator (3.70%) and Ing Ngarso sung Tulodho indicator (7.41%); in indicator of "ngroso" category, most respondents stated that they always "ngroso". Most of the students of PKK are in the category of always "nglakoni", even though the characteristic indicator of wening-bening is in the category of always (14.81%) and sometimes (55.56%).